Поняття та особливості адміністративно-правового статусу органів місцевого самоврядування як суб’єктів забезпечення територіальної оборони України - Романський, І. В.; Romanskyi , I. V. (Форум права. - 2023. - № 3(76). - С. 65-70, 2023)
Визначено специфіку адміністративно-правового статусу органів місцевого самоврядування як суб’єктів забезпечення територіальної оборони України. Узагальнено, що особливостями адміністративно-правового статусу органів місцевого самоврядування як суб’єктів забезпечення територіальної оборони України є наступні: регулюється спеціальним адміністративним законодавством; органи місцевого самоврядування володіють спеціальним набором повноважень та чітко визначену компетенцію; мають певний ступінь автономії в рішенні питань забезпечення територіальної оборони в рамках загальнодержавних стратегій; активно співпрацюють з центральними органами державної влади та військовими структурами для координації дій у сфері територіальної оборони; виконують важливу роль у підготовці та організації мобілізаційних заходів на своїй території.

As of today, research on the state and prospects of improving the administrative-legal status of local self-government bodies as key entities in ensuring the territorial defense of Ukraine is highly relevant. The purpose of this article is to define the specifics of the administrative-legal status of local self-government bodies as subjects responsible for the territorial defense of Ukraine. The research employs the following legal methods: normative-legal analysis to examine existing legislation and norms governing the status of local self-government bodies in the context of territorial defense, legal modeling to develop potential models of the administrative-legal status of local self-government bodies for the purpose of territorial defense, and documentary analysis of official documents, decisions, and resolutions of local self-government bodies pertaining to their roles in territorial defense. Results. It is observed that the administrative-legal status of local selfgovernment bodies as entities responsible for territorial defense constitutes a set of legislatively defined elements that delineate the role of local self-government within the framework of implementing relevant activities and indicate its place within the system of state authorities. Conclusions. In summary, the administrative-legal status of local self-government bodies, serving as entities responsible for ensuring the territorial defense of Ukraine, is characterized by several key attributes. It is governed by specialized administrative legislation, granting these bodies a distinct set of powers and clearly defined competencies. Additionally, they possess a certain level of autonomy in decision-making related to territorial defense, all within the overarching framework of national strategies. These bodies actively collaborate with central government authorities and military structures, ensuring coordinated efforts in the realm of territorial defense. Moreover, they play a significant role in the preparation and organization of mobilization measures within their respective territories.

Установлено содержание и структуру категории "административно-правовой статус". Раскрыта сущность административно-правового статуса органов местного самоуправления. Определена специфика административно-правового статуса органов местного самоуправления как субъектов обеспечения территориальной обороны.
Concept and features of the administrative-legal status of local self-government bodies as subjects of ensuring the territorial defense of Ukraine
Keywords: адміністративно-правовий статус; органи місцевого самоврядування; територіальна оборона; Україна; administrative and legal status; local self-government bodies; territorial defense; Ukraine; административно-правовой статус; органы местного самоуправления; территориальная оборона; Украина